2014
DOI: 10.1145/2641569
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Temporal Linearities in Posed and Spontaneous Smiles

Abstract: Creating facial animations that convey an animator's intent is a difficult task because animation techniques are necessarily an approximation of the subtle motion of the face. Some animation techniques may result in linearization of the motion of vertices in space (blendshapes, for example), and other, simpler techniques may result in linearization of the motion in time.In this article, we consider the problem of animating smiles and explore how these simplifications in space and time affect the perceived genu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Therefore, reviewing the literature from the perspective of cognitive science might be more informative in order to understand and propose a proper technique for real-fake expression prediction. In particular, [11,26] show that small emotional changes in eyes and mount movements can be used to interpret an expression as genuine (real) or deceptive (fake) from the sequence of faces. This indicates that both spatial interdependencies of face parts and their sequential structure should be considered in the final model.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, reviewing the literature from the perspective of cognitive science might be more informative in order to understand and propose a proper technique for real-fake expression prediction. In particular, [11,26] show that small emotional changes in eyes and mount movements can be used to interpret an expression as genuine (real) or deceptive (fake) from the sequence of faces. This indicates that both spatial interdependencies of face parts and their sequential structure should be considered in the final model.…”
Section: Related Workmentioning
confidence: 99%
“…For facial emotions, real-fake expression prediction on a video is slightly different from frame-level emotion classification: 1) Temporal interrelations between face parts should be considered, since temporal consistency is highly critical to categorize human expressions [26]. 2) Emotional changes in eyes and mount movements can be distinct to separate real expressions from fake ones [11].…”
Section: Introductionmentioning
confidence: 99%
“…Automatic recognition of facial expressions from digital images and videos has been explored for years, becoming a multidisciplinary research topic that embraces computer vision, machine learning, psychology, neuroscience, and cognitive sciences. Potential applications of recognizing facial expressions are related with healthcare, surveillance, animation engines, driver safety, creating responsive human-computer interfaces, and more [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Synthetic models of human facial expressions [ 16 18 ] offer exciting possibilities for the study of spatial and temporal aspects of dynamic expressions of emotion. Past research has revealed that spatial and temporal characteristics of dynamic facial expressions can be useful for distinguishing between different types of smiles [ 19 , 20 ]. Furthermore, some studies have shown that the dynamics of facial expressions can have important, real-world economic and social outcomes [ 21 , 22 ], and other studies have examined the role of symmetry (or asymmetry) in dynamic facial expressions [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%